The Incidence of Acute Gastrointestinal Illness in Canada, Foodbook Survey 2014-2015. (19th December 2017) - Thomas, M. Kate; Murray, Regan; Nesbitt, Andrea; Pollari, Frank
Abstract : Acute gastrointestinal illness (AGI) is an important public health issue, with many pathogen sources and modes of transmission. A one-year telephone survey was conducted in Canada (2014-2015) to estimate the incidence of self-reported AGI in the previous 28 days and to describe health care seeking behaviour, using a symptom-based case definition. Excluding cases with respiratory symptoms, it is estimated that there are 0.57 self-reported AGI episodes per person-year, almost 19.5 million episodes in Canada each year. The proportion of cases seeking medical care was nearly 9%, of which 17% reported being requested to submit a sample for laboratory testing, and 49% of those requested complied and provided a sample. Results can be used to inform burden of illness and source attribution studies and indicate that AGI continues to be an important public health issue in Canada.